Review of the subgenus Ammosphex Wilcke, 1942 of the genus Arachnospila Kincaid, 1900 (Hymenoptera: Pompilidae) of the Russian Far East and East Siberia - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2011)
A total of nineteen species are reviewed. Five new species: Arachnospila (Ammosphex) belokobylskii Loktionov and Lelej, sp. nov. (Primorskiy Terr.), A. (A.) orientausa Loktionov and Lelej, sp. nov. (Primorskiy Terr.), A. (A.) rasnitsyni Loktionov and Lelej, sp. nov. (Buryatia), A. (A.) tobiasi Loktionov and Lelej, sp. nov. (Buryatia), and A. (A.) zonsteini Loktionov and Lelej, sp. nov. (Buryatia) are described and illustrated. Hitherto unknown females of A. (A.) eoabnormis Lelej, 1995, A. (A.) kurentzovi Lelej, 1995, A. (A.) kurzenkoi Lelej, 1995, A. (A.) mongolopinata Wolf, 1981, A. (A.) wolfi Lelej, 1995, and A. (A.) yasumatsui Wolf and Móczár, 1972 are described. Three species: Arachnospila (Ammosphex) dschingis Wolf and Móczár, 1972, A. (A.) kaszabi Wolf and Móczár, 1972, and A. (A.) yasumatsui Wolf and Móczár, 1972 are newly recorded from Russia. A key to species for both sexes is given.The synonymy of Psammochares subflavus Haupt, 1929 under Arachnospila clericalis (F. Morawitz, 1889) is confirmed.